DAMPAK GAME ONLINE MOBILE LEGENDS TERHADAP KONSENTRASI BELAJAR SISWA DI SMA NEGERI 1 PAGARALAM - Muhammad Arif Alfaroji; Risma Anita Puriani (IKIP Siliwangi, 2026)
This study aims to determine the effect of the online game Mobile Legends on students' learning concentration at SMA Negeri 1 Pagaralam. The background of this research is based on the widespread use of online games among teenagers, particularly Mobile Legends, which potentially disrupts students' focus and academic achievement. This study uses a quantitative approach with a descriptive correlational method. The sample consisted of 46 students selected through purposive sampling, specifically students who actively play Mobile Legends. The research instrument was a questionnaire that had been tested for validity and reliability. Data were analyzed using simple linear regression techniques. The results of the study show that there is a significant influence between the intensity of playing Mobile Legends and students’ learning concentration. The higher the frequency and duration of play, the lower the level of learning concentration. This is indicated by a significance value (p) of less than 0.05 and a coefficient of determination (R²) that reflects the contribution of the independent variable to the dependent variable. The study concludes that Mobile Legends has a negative impact on students’ learning concentration when played excessively. Therefore, good time management and supervision from both parents and teachers are essential so that students can use technology positively without interfering with their academic activities.